Risk Factors Analysis of Hypertension Incidence at Karangtengah Public Health Center, Wonogiri Regency - Atina Robbiatul Azizah; Angga Mardro Raharjo; Inke Kusumastuti; Cholis Abrori; Pipiet Wulandari (Faculty of Medicine, University of Jember, 2021)
Hypertension is the most common disease found in Karangtengah Health Center, Wonogiri Regency. The incidence of hypertension can be influenced by factors such as: factor that can not be changed consists of age, gender, family history of illness and modifiable factors consisted of obesity, occupation, and smoking history. Of these risk factors, still unknown factors which increse the incidence of hypertension in Karang Tengah Public Health Center. The purpose of this study was to determine the relationship of these risk factors with the incidence of hypertension and the determinants of the incidence of hypertension in Karangtengah Public Health Center, Wonogiri Regency. This type of research is analytic observational with a cross-sectional design. The sample of this study used the total sampling method, namely all medical record data of new adult patients (>26 years) with a history of chronic diseases who came to Karangtengah Public Health Center, Wonogiri Regency in October 2020 and this study was conducted in March 2021. There were 76 patients. Most of the patients had hypertension (n=42; 55.3%), including the category of elderly (n=55; 72.4%), women (n=41; 53.9%). More patients had a family history of disease (n=50; 65.8%), were obese (n=40; 52.6%), had minimal work activities (n=44; 57.9%), and had a history of smoking (n=42; 55.3%). The risk factors associated with the incidence of hypertension were age, gender, family history of disease, BMI, occupation, and smoking history (all p<0.05). Keywords: Hypertension, age, family history, BMI, occupation